Harry Toulmin, The Statutes of Mississippi Territory, Revised and Digested by the Authority of the General Assembly 593 (Natchez, 1807) - (:unkn) unknown (General Publisher, 1807)
Prohibition for people to purchase and trade guns and hunting articles with “any Indian.”
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES